The identity of Chivinia Shestakov (Hymenoptera: Braconidae, Braconinae), with description of a similar species from the Oriental region - Long, Khuat Dang; Achterberg, Cornelis Van; Dzuong, Nguyen Van; Oanh, Nguyen Thi; Mai, Pham Quynh (Zootaxa, 2023)
A peculiar new species from Vietnam (Bracon (Pseudochivinia) tobiasi Long & van Achterberg, sp. nov.) is described and illustrated. It is included in a new subgenus Pseudochivinia Long & van Achterberg, subgen. nov., because it does not fit into the superficially similar subgenus Chivinia Shestakov. The new subgenus shares with Chivinia Shestakov the absence of vein r-m of the fore wing (resulting in the absence of a closed second submarginal cell) but can be distinguished from Chivinia and other subgenera of the genus Bracon Fabricius by the deep and crenulate medio-longitudinal depression of the first metasomal tergite and the different venation. Bracon (Chivinia) zimini Shestakov, 1932 is redescribed and illustrated for the first time.